The magic school bus and the electric field trip - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1997)
Ms. Frizzle takes her class on a field trip through the town's electrical wires so they can learn how electricity is generated and how it is used.
4.2
K-3
K-3
Keywords: Electric power -- Juvenile literature; Electric power distribution -- Juvenile literature; Electricity; Electric power; Electricity; Electric power